A Psychological Distress among People during Covid-19: A Systematic Review - Gupta Shubham Lalbabuprasad (AG Volumes, 2022)
Fear, worry, and tension have been introduced into human existence as a result of Covid-19, an unprecedented problem that is being felt over the world right now. People from many areas of life have had their mental health affected by the Covid-19 epidemic ever since it first appeared. There is little question that the COVID-19 epidemic has disrupted daily life and brought about unexpected changes, prompting strong emotional reactions and a mental health crisis. This research set out to determine the social and psychological aspects that were most likely to cause suffering among the Indian people when a new coronavirus epidemic unfolded there. This article’s goal is to provide an overview of how the widespread spread of Covid-19 virus has contributed to emotional suffering among Indian women. To summarise the effects of the pandemic Covid-19 on subsequent shifts in sleeplessness, anxiety, stress, and depression rates among Indian women, this review was undertaken. Beginning in 2021, we have begun using Google Scholar to seek for papers that meet the review’s inclusion criteria.